Impactos da formação inicial do curso de pedagogia PARFOR nas práticas curriculares de docentes da educação infantil - BEZERRA, Hévila dos Santos (2021)
The present work brings results of the research Impacts of the initial formation of the PARFOR Pedagogy course on the curricular practices of preschool teachers. The objective is to analyze if the curricular practices of the teachers in exercise in Childhood Education are undergoing significant alterations due to the initial formation received, in higher level. The data were collected through training memorial and teacher professionalization elaborated by the participants during the curricular component of the course Didactics and Teacher Training course project, application of a semi-open questionnaire, consisting of the professional profile axes, curricular practice prior to enrollment in the course and perception of changes, and semi-structure interviews. The results point out that one of the most evident changes in the pedagogical practices of the teachers participating, based on their perception, in the research was with regard to teaching methodology, considering that this was one of the main difficulties faced in the pedagogical planning before entering the course. Another perceived change was regarding to the knowledge of the educational theories that the teachers had no understanding, whereas they only counted on the formation of teaching in the middle level, which allows us to consider that this formation was its precarious form. The permanencies prevailed with regard to the evaluation method through opinions, the organizations of the groups remain between division of groups or individual according to the proposal of each activity, and the didactic sequences and projects continue being the main form of organization of contents of teaching.